Danger-associated molecular pattern molecules and the receptor for advanced glycation end products enhance ANCA-induced responses. (11th May 2021) - Page, Theresa H; Chiappo, Derick; Brunini, Francesca; Garnica, Josep; Blackburn, Jack; Dudhiya, Fayaz; Prendecki, Maria; McAdoo, Stephen P; Pusey, Charles D
Abstract: Objectives: The pro-inflammatory activities of the calgranulins and HMGB1 can be counteracted by sRAGE, the soluble form of their shared receptor. To understand the role of these molecules in AAV and their potential as therapeutic targets we have studied (i) the relationship between these DAMPS and disease activity; (ii) the expression of RAGE and sRAGE in biopsy tissue and peripheral blood; and (iii) the effect of these molecules on ANCA-mediated cytokine production. Methods: We examined circulating levels of calgranulins (S100A8/A9 and S100A12), HMGB1 and sRAGE by ELISA. RAGE was examined in AAV kidney and lung biopsies by immunohistochemistry and RAGE expression was monitored in peripheral blood by qPCR. In vitro, the effect of co-stimulating PBMC with ANCA and S100A8/A9 on cytokine production was studied by ELISA. Results: We found significantly raised levels of calgranulins and HMGB1 in active AAV regardless of clinical phenotype (PR3+/MPO+ AAV). Levels of calgranulins showed significant correlations with each other. RAGE protein and message was raised in peripheral blood and in cells infiltrating kidney and lung biopsy tissue, while sRAGE was lowered. Furthermore, ANCA-mediated production of IL-8 from PBMC was significantly enhanced by the presence of S100A8/A9 in a RAGE/TLR4-dependent manner. Conclusions: Raised circulating calgranulins provide a good marker of disease activity in AAV and are unlikely to be counteracted by sRAGE. Increased RAGE expression in AAV indicates receptor stimulation in active disease that may exacerbate ANCA-induced cytokine production. Targeting the RAGE pathway may provide a useful therapeutic approach in AAV.